2017
DOI: 10.2147/ott.s137002
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of C-reactive protein/albumin ratio in human malignancies: an updated meta-analysis

Abstract: PurposeThis study aims to investigate the prognostic value of pretreatment C-reactive protein/albumin ratio (CAR) in human malignancies by an updated meta-analysis.MethodsPubMed, Web of Science, Cochrane Library and Wanfang databases were searched. Pooled hazard ratios (HRs) and odds ratios (ORs) with their corresponding 95% confidence intervals (CIs) were used as effective values.ResultsA total of 25 studies with 12,097 patients were included in this meta-analysis. Pooled results showed that high pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 56 publications
1
61
0
1
Order By: Relevance
“…The CAR has the most satisfying prognostic predicting value among systems based on systemic inflammation. Initially, the prognosis value of CAR was found in the outcome of acute exacerbations of chronic disease by Fairclough et al And the correlation between CAR and tumor was subsequently evaluated in various studies . Kinoshita and his colleagues suggested that CAR may be an independent prognostic marker in patients with HCC, and may have comparable prognostic value with other established inflammation‐based prognostic scores (GPS, mGPS, and NLR) .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The CAR has the most satisfying prognostic predicting value among systems based on systemic inflammation. Initially, the prognosis value of CAR was found in the outcome of acute exacerbations of chronic disease by Fairclough et al And the correlation between CAR and tumor was subsequently evaluated in various studies . Kinoshita and his colleagues suggested that CAR may be an independent prognostic marker in patients with HCC, and may have comparable prognostic value with other established inflammation‐based prognostic scores (GPS, mGPS, and NLR) .…”
Section: Discussionsupporting
confidence: 72%
“…Initially, the prognosis value of CAR was found in 20 And the correlation between CAR and tumor was subsequently evaluated in various studies. 9,21,22 Kinoshita and his colleagues suggested that CAR may be an independent prognostic marker in patients with HCC, and may have comparable prognostic value with other established inflammation-based prognostic scores (GPS, mGPS, and NLR). 9 With a similar result in Kinoshita's study, we proved that the prognostic capacity of CAR was superior to the other inflammation-based prognostic scores.…”
Section: T a B L E 3 Univariate And Multivariatementioning
confidence: 99%
“…These findings further indicated that a positive relationship exists between the CAR and NLR with respect to predicting the prognosis. Furthermore, the CAR has a much stronger prognostic ability than the GPS in pancreatic cancer 26,29 and patients with HCC. 12,26 In addition, this conclusion demonstrated that There were several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly measured laboratory blood values, not necessarily aging biomarkers, also might be interesting for this purpose. [14][15][16] The objective of the current study was to compare the added prognostic value of the aforementioned laboratory parameters (Hb, albumin, and CRP) and the composite scores (GPS, mGPS, and the CRP/ albumin ratio) with the added prognostic value of GA and to evaluate their combined prognostic value for OS in addition to clinical information in patients with cancer. 7 For patients with cancer, various studies have identified several blood values routinely measured at the time of diagnosis as prognostic factors for OS.…”
Section: Introductionmentioning
confidence: 99%
“…Their prognostic value for mortality has been shown in multiple studies with various types of cancer in different settings. [14][15][16] The objective of the current study was to compare the added prognostic value of the aforementioned laboratory parameters (Hb, albumin, and CRP) and the composite scores (GPS, mGPS, and the CRP/ albumin ratio) with the added prognostic value of GA and to evaluate their combined prognostic value for OS in addition to clinical information in patients with cancer.…”
Section: Introductionmentioning
confidence: 99%